Regio- and diastereoselective transition metal-free hydroalkylation of N-allenyl sulfonamides by push-pull 2-alkynylquinolines - Dehghanpour Kalan, Reza; Amiri, Kamran; Rominger, Frank; Balalaie, Saeed; Bijanzadeh, Hamid Reza (Organic & biomolecular chemistry, 2022)
We describe a novel and efficient synthetic strategy to construct the linear homoallylic quinolone structures through the intermolecular addition of 2-alkynylquinoline to N-allenyl sulfonamides. We developed the regio- and diastereoselective transition metal-free hydroalkylation of 1,2-dienes by a structure containing a push-pull system. Moreover, the present work was carried out with a high atom economy, mild reaction conditions, and moderate to high yields.
Gesehen am 09.12.2022